2014
DOI: 10.1371/journal.pone.0100481
|View full text |Cite
|
Sign up to set email alerts
|

CRISPLD2 Is a Target of Progesterone Receptor and Its Expression Is Decreased in Women with Endometriosis

Abstract: Endometriosis, defined as the presence of endometrial cells outside of the uterine cavity, is a major cause of infertility and pelvic pain, afflicting more than 10% of reproductive age women. Endometriosis is a chronic inflammatory disease and lipopolysaccharide promotes the proliferation and invasion of endometriotic stromal cells. Cysteine-rich secretory protein LCCL domain-containing 2 (CRISPLD2) has high affinity for lipopolysaccharide and plays a critical role in defense against endotoxin shock. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 66 publications
1
19
1
Order By: Relevance
“…Since a parallel can be drawn with the ovulatory process in which multiple ECM proteins and ECM modifying enzymes are induced (Table 2 ), we suggest that CRISPLD2 may interact with these proteins and modifying enzymes during ovulation. Interestingly, CRISPLD2 is regulated by progesterone (P4) and its receptor (PGR) in the uterus, its expression is high during decidualization, constitutive during pregnancy and is dysregulated in patients with endometriosis [ 49 ]. A similar P4/PGR-dependent regulation of CRISPLD2 gene expression has been observed in rat granulosa cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since a parallel can be drawn with the ovulatory process in which multiple ECM proteins and ECM modifying enzymes are induced (Table 2 ), we suggest that CRISPLD2 may interact with these proteins and modifying enzymes during ovulation. Interestingly, CRISPLD2 is regulated by progesterone (P4) and its receptor (PGR) in the uterus, its expression is high during decidualization, constitutive during pregnancy and is dysregulated in patients with endometriosis [ 49 ]. A similar P4/PGR-dependent regulation of CRISPLD2 gene expression has been observed in rat granulosa cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The human endometrial samples were collected from Michigan State University’s Center for Women’s Health Research Female Reproductive Tract Biorepository, the Greenville Hospital System, and the University of North Carolina. Samples were collected as previously reported [ 97 , 98 ]. Briefly, to compare gene expression patterns of eutopic endometrium between those with and without endometriosis, 28 samples were collected from proliferative, early, mid, and late secretory phases (n = 7 per phase).…”
Section: Methodsmentioning
confidence: 99%
“…Such alterations in the balance between estrogen and progesterone likely impact fertility and implantation while also promoting the pathogenesis of endometriosis as a disease (50). Progesterone receptor changes and down-stream effects of progesterone (51, 52) are noted in women with endometriosis (53). Park et al suggested that the endometrium of women with endometriosis is more proliferative as a result of endometriosis (54) and we demonstrated the endometrium displays an inappropriate elevation in secretory phase estrogen receptors (ESR1) at the time of implantation (55).…”
Section: Endometriosis and Infertility – What Is The Evidence?mentioning
confidence: 99%